Identifying the Enochic Son of Man as God's word and wisdom. (June 2019) - Winn, Adam
While many interpreters of the Enochic Parables have recognized a connection between the Enochic Son of Man and personified wisdom, this article argues that the Enochic Son of Man should be primarily identified as God's wisdom as well as God's word. To this end, the article argues that (a) the Son of Man is best understood as a divine being rather than an idealized human being, (b) a prominent word and wisdom theology existed in the late Second Temple period, and (c) both similarities between the Enochic Son of Man and word/wisdom as well as the narrative of the Parables support the conclusion that the Enochic Son of Man is an apocalyptic embodiment of God's word and wisdom.